2020
DOI: 10.37396/jsc.v3i2.76
|View full text |Cite
|
Sign up to set email alerts
|

Kebijakan Berbasis Data: Analisis dan Prediksi Penyebaran COVID-19 di Jakarta dengan Metode Autoregressive Integrated Moving Average (ARIMA)

Abstract: Data dan informasi merupakan bagian penting dalam pertimbangan mengambil keputusan terkait penanganan COVID-19. Data COVID-19 baik demografi maupun agregat di Provinsi DKI Jakarta diolah dan dianalisis untuk memberikan informasi mengenai situasi dan kondisi terkini terkait pandemi COVID-19 di Provinsi DKI Jakarta. Data COVID-19 tersebut juga dimanfaatkan untuk analisis prediktif untuk mengetahui perkiraan jumlah kasus COVID-19 di masa depan. Analisis prediktif yang digunakan dalam artikel ini adalah metode Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
0
8
0
6
Order By: Relevance
“…Thus, we consider to apply Seasonal Autoregressive Moving Average (SARIMA) for modelling seasonal pattern in STL Decomposition. The SARIMA(0, 1, 2)(2, 1, 0) 12 shown a significant parameter and minimum AIC, 257.794. The VaR using Variance Covariance simulation by identifying seasonal, trend and noise based the linear combination STL-SARIMA framework which a MAPE results of 0.15 provides sharp and well prediction for extreme value with zero penalty.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, we consider to apply Seasonal Autoregressive Moving Average (SARIMA) for modelling seasonal pattern in STL Decomposition. The SARIMA(0, 1, 2)(2, 1, 0) 12 shown a significant parameter and minimum AIC, 257.794. The VaR using Variance Covariance simulation by identifying seasonal, trend and noise based the linear combination STL-SARIMA framework which a MAPE results of 0.15 provides sharp and well prediction for extreme value with zero penalty.…”
Section: Discussionmentioning
confidence: 97%
“…SARIMA is a developing model from the previous model for data that does not contain seasonality, ARIMA [11]. From several research to forecasting COVID-19 cases using the ARIMA model have been carried out with good modeling accuracy results [12] [13] [14]. ArunKumar, et al used the ARIMA and SARIMA models for forecasting Covid-19 in 16 countries, then they found that the SARIMA model outperformed the ARIMA model in capture the seasonality or trends of the data [15].…”
Section: Seasonal Autoregressive Integrated Moving Average (Sarima) Modelmentioning
confidence: 99%
See 3 more Smart Citations